Gross and histomorphology of the ovary of Black Bengal goat (Capra hircus) - Haque A. (2019)
Ovary plays a vital role in the reproductive biology and biotechnology of female animals. In this study, both the right and left ovaries of the Black Bengal goat were collected from the slaughter houses of different Thanas in the Mymensingh district. For each of the specimens, gross parameters such as weight, length and width were recorded. Then they were processed and stained with H&E for histomorphometry. This study revealed that the right ovary (0.53 ± 0.02 g) was heavier than the left (0.52 ± 0.02 g). The length of the right ovary (1.26 ± 0.04 cm) was lower than the left (1.28 ± 0.02 cm) but the width of the right (0.94 ± 0.02 cm) was greater than the left (0.90 ± 0.03 cm). The diameter of ovarian follicles in the cortex was measured as primordial 39.6 ± 6.61 µm, primary single layer 54.0 ± 4.06 µm, primary multi-layer 147.6 ± 11.04 µm, secondary with C-shaped antrum 449.5 ± 75.71 µm and graafian 1.3 ± 0.20 mm. In the graffian follicle, the thickness of the granulosa cell layer was 79.2 ± 11.04 µm, theca interna 75.76 ± 6.82 µm, theca externa 130.07 ± 12.53 µm and the oocyte diameter was 109.8 ± 5.75 µm. These results will be helpful to manipulate ovarian functions in small ruminants